The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/jopr.13414
|View full text |Cite
|
Sign up to set email alerts
|

Endocrowns Clinical Performance and Patient Satisfaction: A Randomized Clinical Trial of Three Monolithic Ceramic Restorations

Abstract: Purpose:The purpose of this randomized, double-blind, clinical trial was to assess the survival of endocrowns made from three different monolithic ceramic materials, and to evaluate patient satisfaction. Materials and Methods: Fifty-three patients (sixty root canal treated molar teeth) were enrolled. Teeth were prepared to a flat butt-joint margin and randomly divided between three material groups: lithium disilicate-reinforced glass-ceramic, monolithic zirconia and polymer infiltrated hybrid ceramic. Predefin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
(57 reference statements)
2
13
0
Order By: Relevance
“…Clinical follow ups of endocrowns in molar and premolars reported biomechanical failures such as fracture of the restoration, 41–44 adhesive failure/debond, 41,42,44,45 and the facture of the supporting tooth structure; 45,46 these data corroborate with failure patterns reported by the in vitro studies (Tables 3 and 4). Clinical studies reporting follow ups of endocrowns in anterior teeth were not identified.…”
Section: Discussionsupporting
confidence: 81%
“…Clinical follow ups of endocrowns in molar and premolars reported biomechanical failures such as fracture of the restoration, 41–44 adhesive failure/debond, 41,42,44,45 and the facture of the supporting tooth structure; 45,46 these data corroborate with failure patterns reported by the in vitro studies (Tables 3 and 4). Clinical studies reporting follow ups of endocrowns in anterior teeth were not identified.…”
Section: Discussionsupporting
confidence: 81%
“…(Zou, Zhan, Xiang, & Li, 2022 ) However, it should be noted that in another study, an increased incidence of zirconia debonding was reported in comparison to lithium disilicate endocrowns, with three debonded zirconia endocrowns observed after 9, 10, and 13 months of clinical service out of 20 total restorations. (El‐Ma'aita, Abu‐Awwad, Hattar, & Devlin, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…These were mainly observed through the central occlusal groove, indicating less fatigue resistance of these restorations (Saratti et al, 2021 ). Due to the lack of long‐term controlled clinical studies, lithium disilicate ceramics are currently the material of choice for endocrowns, primarily due to its reliable bonding to the resin cement and its long‐term stability (El‐Ma'aita et al, 2022 ).…”
Section: Endocrownsmentioning
confidence: 99%